Production of Cellulose Nanofibrils from Agro-Industrial Residues: Systematic Review and Experimental Design via Glycerol Swelling and Extrusion - Marina R. de Andrade; Rodrigo D. O. Polkowski; Ana Paula B. Gonçalves; Joyce B. Azevedo; Rosana Fialho (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
This study presents the systematic review and analysis of scientific articles on cellulose nanofibril (CNF) production from vegetable fibers, with a focus on environmentally friendly methods. The research followed the PRISMA protocol, selecting works that addressed complete extraction processes starting from vegetal fibers and reporting parameters such as length-to-diameter ratio (L/D), crystallinity, and yield of CNFs. Based on the bibliographic findings, a process flowchart and an experimental design were developed for CNF extraction from peach palm sheath, combining glycerol swelling, single-screw extrusion, and dilute acid hydrolysis (0.4–0.6% H₂SO₄). The choice of this route was based on its potential to promote controlled mechanical shear after glycerol plasticization, facilitating the opening of the cell wall and selective removal of amorphous regions while preserving crystallinity. The proposed methodology, supported by literature evidence, offers a technically feasible and sustainable approach for the valorization of agro-industrial residues, with potential for scaling up to pilot and industrial levels.